DEVELOPMENT OF ALGORITHMS AND SOFTWARE COMPONENTS FOR MODELING OF STRESS-STRAIN STATE OF ROCKS DURING COAL DEPOSITS EXPLORATION - Shevchuk, V.; Ivanik, O.; Lavrenyuk, M.; Saveliev, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Studies of the stress-strain state of technologically modified rock mass with the exploration of coal deposits are carried out by the methods of continuum mechanics, based both on analytical solutions and data of field and laboratory experiments. Analytical solutions provide the ability to do the least costly experiments in a wide range of important factors and environmental parameters. The consideration is given to the algorithm and programme module for the simulation of the stress-strain state of coal-bearing strata. The model of homogeneous elastic solid massive is considered as a base model. Developing of basic schemes was carried out for conditions of plane strain. Rock massive with the layer is modeled as a homogeneous transversely isotropic body. Criteria solutions are established by checking of boundary conditions. In order to solve the task of the distribution of stresses in the rock massive, which is modeled as a linear deformable environment around the excavation of any cross-sectional shape, the appropriate type of the unit disk functions was determined. The graphical modeling of the analytical algorithm calculated the stress-strain state of the geological massif with the excavation of any shape was carried out. The software application of the developed algorithm is presented.
Keywords: stress-strain stateб; coal layer; algorithm; simulation; software implementation